Facile preparation of graphene nitride by irradiating MHz ultrasound - Susumu Nii; Hiroki Ueda; Masami Aono; Kei Mizuta; Takashi Goshima (Ultrasonics Sonochemistry, 2022)
The present study aimed at developing a simple sonochemical method to prepare graphene nitride from the mixture of graphite and aqueous ammonia solution. Ultrasound of 1.6 MHz was irradiated to the sample in a fabricated sonoreactor at predetermined ultrasonic power and duration. The one-pot method succeeded in the preparation of graphene nitride. The generation was proven by XPS analysis in finding N1S peak in the spectrum. Detail analysis of N1s peak suggested that the major nitrogen species was pyrrolic type. Furthermore, the presence of CO bond proved the oxidation by OH radical. The reaction product had the value of N/C as high as 0.08, which is comparable to reported values for ultrasonic preparation of graphene nitride. The fact indicates that the significance of chemical effects of MHz range ultrasound, and the finding of the simple preparation method will accelerate practical application of graphene nitride.